2020
DOI: 10.1101/2020.05.06.20092049
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Study of Hepatitis C Virus infection among multi-transfused patients with inherited β-globin synthesis gene defect, in the eastern region of India

Abstract: Post transfusion acquired HCV infection is common in high risk group individuals such as b-thalassemia patients who depend on regular blood transfusions. This study was conducted to determine the prevalence, genotype distribution, transmission dynamics and correlation of patients age and gender with spontaneous clearance of HCV in multi-transfused b-thalassemia patients, in the state of West Bengal, India. HCV RNA was first detected, using RT-PCR, from serum samples collected from HCV seropositive b-thalassemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 42 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…Many studies reported an association between injections drug user (IDU), female sex workers (FSW), men sex with men (MSM) and HCV, and some study reported associated risk patient; β-thalassemia, visceral leishmaniasis, jaundice, dialysis, three studies combined measure 12% prevalence in pregnant women, and also reported slum population and primitive groups with 6% prevalence (Table 2). 1,4,8,[14][15][16][17][18][19]20,22,23…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies reported an association between injections drug user (IDU), female sex workers (FSW), men sex with men (MSM) and HCV, and some study reported associated risk patient; β-thalassemia, visceral leishmaniasis, jaundice, dialysis, three studies combined measure 12% prevalence in pregnant women, and also reported slum population and primitive groups with 6% prevalence (Table 2). 1,4,8,[14][15][16][17][18][19]20,22,23…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence of active HCV infection in some of these transfusion centers was as high as 81%, because the South Asian countries, including India, have been derived by voluntary and paid blood donors. 3,4 HCV infection varies considerably from country to country, probably because of cultural factors and social habits that influence HCV transmission. Transfusion transmitted infections (TTIs) are a major problem associated with blood transfusion practices).…”
Section: Introductionmentioning
confidence: 99%